Deficiencies in Natural Killer Cell Numbers, Expansion, and Function at the Pre-Neoplastic Stage of Pancreatic Cancer by KRAS Mutation in the Pancreas of Obese Mice - Kaur, Kawaljit; Chang, Hui-Hua; Topchyan, Paytsar; Cook, Jessica Morgan; Barkhordarian, Andre; Eibl, Guido; Jewett, Anahid (Frontiers in Immunology, 2018)
The combined/synergistic effect of genetic mutation of KRAS in the pancreas and obesity, a life-style factor on suppression of natural killer (NK) cells at the pre-neoplastic stage of pancreatic cancer has not been investigated and is the subject of this report. Obese mice with KRAS (KC) mutation in the pancreas fed with high-fat calorie diet (HFCD) exhibit severe deficiencies in the NK cell expansion and function at the pre-neoplastic stage of pancreatic cancer. Decreased NK cell-mediated cytotoxicity is observed in the peripheral blood, spleen, pancreas, and peri-pancreatic adipose tissue in obese KC mice, whereas in bone marrow an increased NK cell-mediated cytotoxicity is observed when compared to lean WT mice fed with control diet (CD). Obese KC mice on HFCD demonstrated the least ability to expand NK cells or induce NK cell-mediated cytotoxicity when compared to the other groups of mice. Indeed, the following profile WT/CD > WT/HFCD > KC/CD > KC/HFCD was seen for the ability to expand NK cells or mediate cytotoxicity among four groups of mice in spleen, peripheral blood, pancreas, and peri-pancreatic adipose tissue. Sorted NK cells from the splenocytes of four groups of mice also exhibited the same profiles for the cytotoxicity as the unsorted splenocytes, and a decreased IFN-γ secretion could be seen in cultures of NK cells from KC mice fed with either CD or HFCD. Cultures of NK cells with autologous monocytes from obese KC mice fed with HFCD exhibited decreased cytotoxicity and IFN-γ secretion, whereas cultures of allogeneic NK cells from WT mice fed with CD with osteoclasts of obese mice fed with HFCD demonstrated decreased cytotoxicity but augmented IFN-γ secretion. Increased IL-6 along with decreased IFN-γ and cell-mediated cytotoxicity by the NK cells, within NK-adipose tissue of KC/HFCD mice, may provide safe microenvironment for the expansion of pancreatic tumors.